Motivation and Anxiety in Tennis Players - E. Cervelló; F.J. Santos-Rosa; R. Jiménez; A. Nerea; T. García (Asociación Española de Ciencias del Deporte, 2010)
This work studied the "goals achievement theory;" how dispositional goal orientation and the perception of the motivational climate are related to the different components of competitive anxiety (cognitive anxiety, somatic anxiety and self-confidence) in high-level tennis players. To the accomplish this objective structural equation modelling was employed (SEM). The results show that perception of the motivational climate that tennis players perceive is related to dispositional goal orientation. Results also show positive relationships between perception of ego involving motivational climate and somatic and cognitive components of anxiety. On the other hand, results show that ego orientation is a negative predictor of cognitive anxiety. Finally, results show that task orientation is a positive and significant predictor of self-confidence. KEY WORDS: Goal orientation, motivational climate, competitive state anxiety, tennis